Prospective evaluation of an indwelling esophageal balloon dilatation feeding tube for treatment of benign esophageal strictures in dogs and cats. (20th February 2018) - Tan, Desmond K.; Weisse, Chick; Berent, Allyson; Lamb, Kenneth E.
Abstract : Background: Despite multiple dilatation procedures, benign esophageal strictures (BES) remain a recurring cause of morbidity and mortality in dogs and cats. Objective: Investigate the use of an indwelling Balloon Dilatation esophagostomy tube (B‐Tube) for treatment of BES in dogs and cats. Animals: Nine dogs and 3 cats. Methods: Animals with BES were recruited for our prospective study. Endoscopic and fluoroscopic evaluation of the esophagus and balloon dilatation were performed under general anesthesia, followed by placement of an indwelling B‐Tube. The animals' owners performed twice daily at‐home inflations for approximately 6 weeks. Repeat endoscopy was performed before B‐Tube removal. Animals were reevaluated for changes in modified dysphagia score (MDS) after B‐Tube removal. Results: The B‐Tube management was relatively well tolerated and effective in maintaining dilatation of a BES while in place. These animals underwent a median of 2 anesthetic episodes and were monitored for a median of 472 days (range, 358‐1736 days). The mean MDS before treatment was 3.1 ± 0.5/4.0 and final follow‐up MDS were significantly ( P  < .0001) improved at 0.36 ± 0.65/4.0. Eleven of 12 animals (91.7%) had improved MDS at the end of the follow‐up period, with 8/12 (66.7%) having an MDS of 0/4, 2/12 (16.7%) an MDS of 1/4, and 1/12 (8.3%) an MDS of 2/4. One dog died. Conclusions and Clinical Importance: The B‐Tube offers an effective, and more economical method, and often decreased anesthetic time to repeated balloon dilatation procedures for the treatment of BES in dogs and cats.